PENGARUH KEAMANAN, KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN MAXIM DI KOTA BATAM : PENGARUH KEAMANAN, KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN MAXIM DI KOTA BATAM - Manihuruk, Elida Wati (SCIENTIA JOURNAL, 2025)
Maxim is an online transportation service that has grown rapidly in various countries, including Indonesia. The service offers a variety of transportation options, from taxis to motorcycle taxis, and even includes goods and food delivery services. This study aims to determine the influence of security, trust, and satisfaction on customer loyalty. Maxim in Batam City. This type of research is a quantitative research, the population of this study is the people of Batam City with a sampling technique using the Jacob Cohen formula so that a sample of 204 people was obtained and data processing using SPSS 25. From this study, the results were obtained that security had a positive and significant effect on customer loyalty with a calculated t value greater than the table t, which was 6.019 >1.971 with a significant value of 0.000 <0.05. The trust variable had a positive and significant effect on customer loyalty with a calculated t value greater than the table t, which was 7>3271.971 with a significant value of 0.000 <0.05, and the satisfaction variable also had a positive and significant effect on customer loyalty with a t-value of 6.050>1.971 with a significant value of 0.000 <0.05. Keywords: Security, Trust, Satisfaction, Customer Loyalty.